2007
DOI: 10.1073/pnas.0705346104
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of human neural stem cell differentiation in Alzheimer (APP23) transgenic mice by phenserine

Abstract: In a previous study, we found that human neural stem cells (HNSCs) exposed to high concentrations of secreted amyloid-precursor protein (sAPP) in vitro differentiated into mainly astrocytes, suggesting that pathological alterations in APP processing during neurodegenerative conditions such as Alzheimer's disease (AD) may prevent neuronal differentiation of HNSCs. Thus, successful neuroplacement therapy for AD may require regulating APP expression to favorable levels to enhance neuronal differentiation of HNSCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 49 publications
(57 reference statements)
1
69
1
Order By: Relevance
“…The capacity of NSCs for CNS migration and neural cell differentiation makes these cells attractive resources for cell-based therapy, not only in EAE, but also in other types of neurodegenerative diseases (32,33). Systemic and i.c.v.…”
Section: Discussionmentioning
confidence: 99%
“…The capacity of NSCs for CNS migration and neural cell differentiation makes these cells attractive resources for cell-based therapy, not only in EAE, but also in other types of neurodegenerative diseases (32,33). Systemic and i.c.v.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this fundamental problem, researchers have injected stem cells or stem cell-derived neurons into various brain regions in AD mouse models with the hope of restoring brain function. While in some cases the transplanted animals showed no improvement, in others stem cell transplantation produced a substantial improvement in cognitive function (Blurton-Jones et al, 2009;Marutle et al, 2007). The mechanisms by which these stem cell transplants achieved behavioral improvements are however controversial; optimistic researchers have suggested that the improvement is due to the replacement of damaged neurons (Marutle et al, 2007).…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…While in some cases the transplanted animals showed no improvement, in others stem cell transplantation produced a substantial improvement in cognitive function (Blurton-Jones et al, 2009;Marutle et al, 2007). The mechanisms by which these stem cell transplants achieved behavioral improvements are however controversial; optimistic researchers have suggested that the improvement is due to the replacement of damaged neurons (Marutle et al, 2007). However, more conservative investigators indicate that the injected stem cells did not replace damaged neurons but instead released trophic factors (e.g., BDNF, brain derived neurotrophic factor; NT-3, neurotrophin 3) that support cell survival and neuronal plasticity (Blurton-Jones et al, 2009).…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…Phenserine, a novel AChEI drug, has been shown to decrease A levels by regulating APP translation [144], as shown both in cell cultures and in mouse brain [145,146]. The effect of long-term treatment with phenserine has also been evaluated in patients with mild AD by PET, using a ligand, PIB, which allows detection of amyloid deposits [147].…”
Section: Therapeutic Evaluations In Mouse Mod-els Of Admentioning
confidence: 98%